AB1181 SHOULD A COMBINED RHEUMATOLOGY-PULMONOLOGY INTERSTITIAL LUNG DISEASE SERVICE BE CONFINED TO TERTIARY CENTRES - A SERVICE EVALUATION. (2nd June 2020) - Salama, K.; Ramsundar, N.; Joshi, V.; Nisar, M. K.
Abstract : Background: Interstitial lung disease is a well described extra-articular manifestation in a range of rheumatic diseases. It carries significant morbidity and mortality. Management of rheumatic diseases associated ILD (r-ILD) requires expertise as the needs of such patients are complex and treatment options limited. Historically, such complex ILD has been managed in tertiary referral centres. Objectives: We set up a combined service incorporating both rheumatology and respiratory domains in a district general hospital (DGH) to help patients avoid long journeys and improve their experience whilst focusing on an integrated care pathway. We evaluated the outcomes of the first set of patients managed in this proof-of-concept service model. Methods: Referrals were accepted from any hospital specialist involved in the management r-ILD. They were triaged by lead ILD pulmonologist to monthly ILD MDT comprising a rheumatologist, respiratory physician, a radiologist and ILD specialist nurse. Appropriate patients were booked into combined clinic, run by the respective rheumatology and chest specialists with ILD interest, attracting a multi-speciality tariff. All the data was recorded electronically with full access to demographics, disease parameters, investigations and drug management. Results: 89 patients were included in this proof-of-concept. Mean age was 66.1 yrs (19-90 yrs) and 44% (n=39) were male. 35 (40%) had RA, 34 (39%) had CTD, eight (10%) had sarcoidosis, five had IPAF and seven others. Most predominant HRCT pattern was NSIP (n=53, 60%) followed by UIP (n=23, 21%), sarcoid (n=10, 12%) and miscellaneous (LIP and mixed). Mean FVC was 2.64 L/min (1.93-4.13) with DLCOc of 52.7% (28.9-90.1%) predicted. Only two patients had all antibodies negative whilst 87 had at least one antibody positive with ANA being the most common (n=28). Most (83%) patients were treated with immunomodulators including nine with rituximab. 39 (44.3%) patients had significant improvement in clinical, imaging and pulmonary parameters with DLCOc improving to 56.57% and FVC to 2.70 L/min. There were similar improvements in six minute walk test. 17 patients died and 20 patients required long term oxygen therapy. Conclusion: This proof-of-concept real world study confirms the utility of a combined specialist service in a district general hospital. Nearly half of this complex and resource intensive patient cohort had good clinical outcomes and derived benefit from the expertise in one room. Feedback from both patients and referrers was unanimously positive. No patient required tertiary centre referral and all could be managed adequately in the clinical setting. Our report confirms that r-ILD can be managed in a DGH setting with a stream-lined service offering clear benefits to patients. We would argue that r-ILD service, congruent to satellite pulmonary hypertension clinics in secondary care with hub-and-spoke model liaison with tertiary centre, can be established on similar principles and could help over-stretched tertiary care with repatriation of services whilst helping develop local expertise in the management of chronic ILD. Disclosure of Interests: Karim Salama: None declared, Natasha Ramsundar: None declared, Vijay Joshi: None declared, Muhammad Khurram Nisar Grant/research support from: Muhammad Nisar undertakes clinical trials and received support (including attendance at conferences, speaker fees and honoraria) from Roche, Chugai, MSD, Abbvie, Pfizer, BMS, Celgene, Novartis and UCB, Consultant of: Muhammad Nisar undertakes clinical trials and received support (including attendance at conferences, speaker fees and honoraria) from Roche, Chugai, MSD, Abbvie, Pfizer, BMS, Celgene, Novartis and UCB, Speakers bureau: Muhammad Nisar undertakes clinical trials and received support (including attendance at conferences, speaker fees and honoraria) from Roche, Chugai, MSD, Abbvie, Pfizer, BMS, Celgene, Novartis and UCB